Model-based patterns of cardiovascular risk factors in Mozambique - Padrão, Patrícia (2015)
Background: Risk factors for cardiovascular diseases tend to cluster, although evidence from settings under epidemiological transition is scarce. Aim: To identify patterns of clustering of cardiovascular risk factors and to quantify their association with sociodemographic characteristics, in Mozambique. Subjects and methods: A national representative sample (n ¼ 3323) of subjects aged 25-64 years was evaluated in 2005, using the World Health Organization Stepwise Approach to Chronic Disease Risk Factor Surveillance (STEPS). Patterns of joint exposure to high blood pressure, high fasting blood glucose, high body mass index, smoking, excessive alcohol consumption, low fruit/vegetables intake and insufficient physical activity were identified through latent class analysis. Results: Three patterns were identified among women: (1) ''healthier'', lower frequency of most risk factors (53.0%); (2) ''hypertension-overweight'' (21.1%), more frequent among older and urban subjects; and (3) ''hypertension-smoking-alcohol'' (25.9%), whose frequency increased with age and decreased with education. In men, two clusters were identified: (1) 'hypertensionoverweight'' (30.1%); and (2) ''smoking'' (69.9%). The frequency of the latter pattern was higher in urban areas and increased with age and education. Conclusion: Hypertension, overweight/obesity, smoking and excessive alcohol intake defined the main clusters of cardiovascular risk factors. This should be considered when planning prevention and control strategies for cardiovascular diseases in Mozambique.